Evaluasi Degradasi Isolasi Motor akibat Multi-factor Aging berdasarkan Indeks Polarisasi dan SEM-EDX - Mochammad Wahyudi; Dimas Anton Asfani; I Made Yulistya Negara; Daniar Fahmi; I Gusti Ngurah Satriyadi Hernanda (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
The operation of induction motor affected by stress factor causes insulation degradation. This degradation can be observed from changes in insulation characteristics, including electrical, physical, and chemical. This study aimed to evaluate the insulation resistance (IR) and polarization index (PI) since the induction motor condition was good until burned out. Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy ( SEM-EDX) testing was also carried out to analyze changes in microstructure, morphological characteristics, and chemical composition in stator windings. In addition, X-ray powder diffraction ( XRD) testing was presented to validate that the damaged insulation was caused by the given stress. To accelerate degradation of insulation, induction motor in service condition was subjected by a lot of pressure simultaneously, including thermal, moisture, and salt contamination. The accelerated aging testing was gradually conducted according to three schemes with different pressure levels. The results showed that the applied stresses could accelerate the insulation aging. A significant decrease of IR and PI values was found in the third scheme, as the IR value was less than 5 MΩ and the PI value was 0.6 (danger category). The insulation failure was achieved at a total duration of testing for 222 hours. The results of SEM-EDX and XRD testing showed the presence of mineral deposits from water vapor, salt contaminants, cracks, and fracture on the insulation surface.